Modest Filter Socialization for Wastewater Discharge Resulted From Laundry Activity in Palangka Raya - N. Novrianti; Nani Apriyani (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The increase of laundry service for clothes in Palangka Raya will affect the amount of waste generated from the service. The waste is discharged directly without undergoing the necessary process. Therefore, it has the potential to cause environmental pollution, in particular, water. The community service program aims at socializing the filtering of laundry wastewater to the laundry services. The filtering process is by absorption and filtration methods of the surfactant in the waste not to exceed the standard. The community service program's outcome target is to socialize the filter of laundry waste towards the laundry service owners at Palangka Raya city. The research finding proves that there has not been any filtering system to minimize environmental pollution, mostly water, due to the detergent material. Laundry services usually use detergent for the washing to consider its cleaning characteristics that are more effective than ordinary washing soap. The detergent's main content is an ionic compound tripolyphosphate functioning as a builder and surfactant. The socialization towards laundry services is by directing them to not discharge the wastewater directly into drainage; therefore, the wastewater can settle and deposited.